Comparing data quality and cost from three modes of on-board transit surveys. (February 2017) - Agrawal, Asha Weinsten; Granger-Bevan, Stephen; Newmark, Gregory L.; Nixon, Hilary
Abstract: Many transit agencies invest substantial resources in surveying their passengers to generate data used for planning, marketing, and equity analyses. Within the industry, there is considerable interest in replacing traditional paper-based self-complete surveys with new approaches that might lower costs or generate better quality data. However, very limited research has been done to identify the relative performance of different transit passenger survey modes. This paper begins to fill that gap. The research investigates the relative data quality for three different bus passenger survey methods distributed or administered on the transit vehicle: self-complete paper surveys, interviewer-assisted tablet-based surveys, and self-complete online surveys. The research used an experimental design, with the same survey questionnaire distributed via the three survey modes. All factors about the survey and distribution process were kept identical to the extent feasible, so that the only variation would be the survey mode itself. The findings by survey mode are compared in terms of the overall response and completion rates, the completion rate for individual questions, respondent demographics, and labor costs per complete. The study results suggest that many agencies may still find the old-fashioned, low-tech paper survey to be the best option for bus passenger surveys. The paper mode required less labor per complete, and for many of the metrics discussed it generated data that was as good as—or better than—the tablet survey. In addition, the findings suggest that online survey invitations distributed on the transit vehicle are not a good option because they were labor intensive and had very low response rates. Highlights: No one survey mode is "best" by all measures. Survey mode performance depends on how response or completion rate is defined. Paper surveys required the fewest surveyor and data entry hours per completed survey. Online surveys performed poorly by almost every measure tested.